La planificación estratégica y la gestión administrativa en la industria Prolácteos del cantón Latacunga. - Alcocer Herrera, Eunice Lizeth (2022)
The objective of this research project was to design a strategic planning model that supports administrative management in the Prolácteos industry of the Latacunga canton, with which it was identified how strategic planning contributes to the administrative management of the business. The research methodology was a qualitative and quantitative approach, descriptive with an application scope, the population under study on the one hand are the 8 workers and on the other the client portfolio that corresponds to 81 establishments according to the company's database, from which a sample with an error of 5% and a confidence level of 95% was obtained, corresponding to 67 businesses between bakeries, shops, cafeterias and market stalls. In his diagnosis, the absence of planning, organization, direction and control in the medium and long term, little publicity and promotion, weak training, artisanal production and duplication of functions, in addition to the economic crisis due to Covid-19 and competition, were detected. Advantageously, the company has experience in cheese production and up-to-date operating permits and regulations. To contrast the information, a plan was designed with seven perspective strategies: financial, customers, internal processes, growth and learning, and the environment.